Ultra-High Resolution Characterization of Domain Motions and Correlations by Multi-Alignment and Multi-Reference RDC NMR - Fisher, Charles K. (2008)
Nuclear Magnetic Resonance (NMR) residual dipolar couplings (RDC) provide a unique opportunity for spatially characterizing complex motions in biomolecules with timescale sensitivity extending up to milliseconds. Up to five motionally averaged Wigner rotation elements, [Formula: see text] , can be determined experimentally using RDCs measured in five linearly independent alignment conditions and applied to define motions of axially symmetric bond vectors. Here, we show that up to twenty-five motionally averaged Wigner rotation elements, [Formula: see text] , can be determined experimentally from multi-alignment RDCs and used to characterize rigid-body motions of chiral domains. The twenty-five [Formula: see text] elements form a basis set that allows one to measure motions of a domain relative to an isotropic distribution of reference frames anchored on a second domain (and vice versa), thus expanding the 3D spatial resolution with which motions can be characterized. The twenty-five [Formula: see text] elements can also be used to fit an ensemble consisting of up to eight equally or six unequally populated states. For more than two domains, changing the identity of the domain governing alignment allows access to new information regarding the correlated nature of the domain fluctuations. Example simulations are provided that validate the theoretical derivation and illustrate the high spatial resolution with which rigid-body domain motions can be characterized using multi-alignment and multi-reference RDCs. Our results further motivate the development of experimental approaches for both modulating alignment and anchoring it on specifically targeted domains.